Genetic variants within microRNA‐binding site of RAD51B are associated with risk of cervical cancer in Chinese women. (23rd June 2016) - Hang, Dong; Zhou, Wen; Jia, Meiqun; Wang, Lihua; Zhou, Jing; Yin, Yin; Ma, Hongxia; Hu, Zhibin; Li, Ni; Shen, Hongbin
Abstract : This study provides the first evidence that genetic variants within miRNA‐ binding site of RAD51B may modify the susceptibility to cervical cancer. Abstract: RAD51B plays a central role in homologous recombinational repair (HRR) of DNA double‐strand breaks (DSBs), which is important to prevent genomic instability, a hallmark of cancer. Recent studies suggested that common genetic variants of RAD51B may contribute to cancer susceptibility. In this study, we aimed to investigate whether potentially functional variants within miRNA‐binding sites of RAD51B are associated with risk of cervical cancer. A total of 1486 cervical cancer patients and 1536 cancer‐free controls were enrolled, and two genetic variants, rs963917 (A > G) and rs963918 (T > C), were genotyped in all participants. Using multivariate logistic regression analyses, we found that G allele of rs963917 conferred lower risk of cervical cancer compared to A allele (adjusted OR = 0.89, 95% CI = 0.80–0.99, P  =   0.039). Similarly, rs963918 allele C was associated with a decreased risk for cervical cancer compared with allele T (adjusted OR = 0.84, 95% CI = 0.74–0.94, P  =   0.004). Haplotype analyses showed that haplotype GC was also correlated with lower risk (OR = 0.83, 95% CI = 0.73–0.95, P  =   0.005) compared with the most common haplotype AT. In summary, our study suggested that miRNA‐binding site genetic variants of RAD51B may modify the susceptibility to cervical cancer, which is important to identify individuals with differential risk for this malignancy and to improve the effectiveness of preventive intervention.